Physical performance preparation for the cerebral palsy football world cup: A team study - Peña-González, I.; Moya-Ramón, M. (Apunts Sports Medicine, 2023)
This study is the first study to show a cerebral palsy (CP) football physical performance preparation period for a World Cup. The physical performance improvement of fourteen international players belonging to the Spanish national team was assessed during five consecutive training camps (TCs) before the 2022 World Cup. The results revealed significant improvements (t = 1.75-4.24; p< .05) in the analysed variables between the first and the final TC, with changes ranging from 5.3% to 78.2% and effect sizes from 0.64 to 1.46 (moderate to large). All tests showed a consistent tendency to improve along the TCs and the pairwise analysis showed higher improvements in TC3 and TC5 compared to the values of TC1. This data could provide practical information to CP football coaches and practitioners since this is the first time that a physical performance preparation of a CP football team for a World Cup is studied.